If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3-10w)+8w=18-3(w-5)
We move all terms to the left:
(3-10w)+8w-(18-3(w-5))=0
We add all the numbers together, and all the variables
(-10w+3)+8w-(18-3(w-5))=0
We add all the numbers together, and all the variables
8w+(-10w+3)-(18-3(w-5))=0
We get rid of parentheses
8w-10w-(18-3(w-5))+3=0
We calculate terms in parentheses: -(18-3(w-5)), so:We add all the numbers together, and all the variables
18-3(w-5)
determiningTheFunctionDomain -3(w-5)+18
We multiply parentheses
-3w+15+18
We add all the numbers together, and all the variables
-3w+33
Back to the equation:
-(-3w+33)
-2w-(-3w+33)+3=0
We get rid of parentheses
-2w+3w-33+3=0
We add all the numbers together, and all the variables
w-30=0
We move all terms containing w to the left, all other terms to the right
w=30
| 14=-5w+3(w+2) | | 2(d+10)=5(d+8)-2 | | 3u-10=-6u+8 | | 4÷3w-12=2÷3w | | 5q=-5+4q | | 6x+3=14x-3 | | 6-x=33 | | 7m-15=4m+9 | | -r-10=10+10-7r | | 4z/10-1=4 | | -8x+2x=92 | | 4x+5x-6=(3x-1) | | -6+4z=-2+3z | | x=400*(200+x)/(400+(200+x)) | | 1/x=1/400+1/(200+x) | | -9+x=-19 | | 7v+16=11v | | -2h=9-3h | | -9r-3=114 | | -g÷-6=-4 | | -10s+8=5s-7 | | 10n=7n+12 | | A=2w+3/16 | | 0.2x-1.8/5=4.2 | | -1=x-4/6 | | x/8+8=6 | | 21=t-9 | | -9-8b=55 | | -9s=-7s-6 | | n=-7+16 | | 5-x=12. | | 9p^2=6=42 |